2014
DOI: 10.1039/c3sm53113a
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal stress and structure evolution in dynamically sheared polymer-like micellar solutions

Abstract: The complex, nonlinear flow behavior of soft materials transcends industrial applications, smart material design and non-equilibrium thermodynamics. A long-standing, fundamental challenge in soft-matter science is establishing a quantitative connection between the deformation field, local microstructure and macroscopic dynamic flow properties i.e., the rheology. Here, a new experimental method is developed using simultaneous small angle neutron scattering (SANS) and nonlinear oscillatory shear rheometry to inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
43
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 41 publications
(44 citation statements)
references
References 39 publications
1
43
0
Order By: Relevance
“…(11)- (14), which we calculated from the Giesekus model coincide quantitatively with the results of Gurnon and Wagner [86]. As Eq.…”
Section: Analytical Solutions For Steady-state Shear Flowsupporting
confidence: 67%
See 1 more Smart Citation
“…(11)- (14), which we calculated from the Giesekus model coincide quantitatively with the results of Gurnon and Wagner [86]. As Eq.…”
Section: Analytical Solutions For Steady-state Shear Flowsupporting
confidence: 67%
“…The extensive experiments of Calin, Wilhelm, and Balan revealed that, besides studying the shear-thinning properties, LAOS experiments could successfully be applied in order to measure the nonlinear α-parameter (mobility factor) of the Giesekus model [85]. An extensive description of LAOS measurements in aqueous solutions of banding and non-banding wormlike micelles and the evaluation of the Giesekus model parameters were recently performed by Gurnon and Wagner [86]. The mentioned last three publications have extensively analyzed the non-linear properties of the shear stress in LAOS experiments.…”
Section: Introductionmentioning
confidence: 98%
“…Using flow SALS, (Ultra)SAXS or SANS a butterfly pattern is observed in the velocityvorticity plane of flow [17,[24][25][26] accompanied by a similar anisotropy in the velocity-velocity gradient plane [17,26]. Detailed flow-SANS measurements show how these anisotropic structure factors (on length scales corresponding to a few particle diameters) correlate with rheology [17,29]. USAXS and SALS measurements show how these anisotropic microstructures extend to large length scales, beyond hundreds of particle diameters [26], which is consistent with the recent microscopic investigations.…”
Section: Introductionmentioning
confidence: 99%
“…Since startup experiments are susceptible to wall slippage [Gurnon et al (2014) b. Shear hysteresis. Shear hysteresis characterizations have been widely studied in gel-like fluids with thixotropic and viscoelastic properties [Bird and Marsh (1968); Divoux et al (2013); Mewis and Wagner (2009);Yoon et al (2014)].…”
Section: Hydrophobic Hncmentioning
confidence: 99%